The time and space of Richard Coudenhove-Kalergi’s Pan-Europe, 1923-1939 - Thorpe, Benjamin J. (2018)
This thesis investigates the historical geographies of the Pan-European Union, and its founder and leader Count Richard Coudenhove-Kalergi, focusing in the main on the period from 1923 to 1939. A mixed-race Austrian aristocrat, philosopher and writer who made it his life’s mission to see Europe politically united, Coudenhove-Kalergi’s was a singular life, which he used to his advantage by weaving his life story into his political campaigning. The thesis opens by investigating the relationship between a life lived and a life told, and about the consequences for researchers attempting to recover his biography.